Psycho-physical dualism today : an interdisciplinary approach - Antonietti, Alessandro, 1960-; Corradini, Antonella; Lowe, E. J. (E. Jonathan) (Lexington Books, 2008)
Philosophers and scientists have recently been showing renewed interest in dualistic conceptions of the human mind, owing to growing acknowledgment of the failings of materialism and reductionism in contemporary philosophical and scientific thought. This.